Reconstruction of linear functionals on classes of analytic functions of two variables on the basis of generalized information - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For classes of analytic functions defined in terms of the two-dimensional Hadamard composition, we propose a renewal method for linear functionals based on blending constructions. The best renewal methods are indicated, and the exact estimates of errors are given.